"The merits and demerits of Ibsen's great play": the reception of the Novelty Theatre Company matinée performance A doll's house, Theatre Royal, Brighton England, June 20th 1889 - Jill Farleigh Wolfe (Nordlit: Tidsskrift i litteratur og kultur, 2015)
“Merits and Demerits of Ibsen’s great play”: The Reception of a performance of A Doll’s House by the Novelty Theatre Company at The Theatre Royal Brighton England June 20th 1889.